SenseCam reminiscence and action recall in memory-unimpaired people - Seamon, John G.; Moskowitz, Tacie N.; Swan, Ashley E.; Zhong, Boyuan; Golembeski, Amy; Liong, Christopher; Narzikul, Alexa C.; Sosan, Olumide A. (Memory (Hove), 2014)
Case studies of memory-impaired individuals consistently show that reminiscing with SenseCam images enhances event recall. This exploratory study examined whether a similar benefit would occur for the consolidation of memories in memory-unimpaired people. We tested delayed recall for atypical actions observed on a lengthy walk. Participants used SenseCam, a diary, or no external memory aid while walking, followed by reminiscence with SenseCam images, diary entries, or no aid, either alone (self-reminiscence) or with the experimenter (social reminiscence). One week later, when tested without SenseCam images or diary entries, prior social reminiscence produced greater recall than self-reminiscence, but there were no differences between memory aid conditions for action free recall or action order recall. When methodological variables were controlled, there was no recall advantage for SenseCam reminiscence with memory-unimpaired participants. The case studies and present study differ in multiple ways, making direct comparisons problematic. SenseCam is a valuable aid to the memory impaired, but its mnemonic value for non-clinical populations remains to be determined.